Using the two-way shape memory effect of NiTi to control surface texture for cellular mechanotransduction. (8th June 2018) - Liang, Yuan; Qin, Haifeng; Hou, Xiaoning; Doll, Gary L; Ye, Chang; Dong, Yalin
Abstract: Mechanical force can crucially affect form and function of cells, and play critical roles in many diseases. While techniques to conveniently apply mechanical force to cells are limited, we fabricate a surface actuator prototype for cellular mechanotransduction by imparting severe plastic deformation into the surface of shape memory alloy (SMA). Using ultrasonic nanocrystal surface modification (UNSM), a deformation-based surface engineering technique with high controllability, micro surface patterns can be generated on the surface of SMA so that the micro-size cell can conform to the pattern; meanwhile, phase transformation can be induced in the subsurface by severe plastic deformation. By controlling plastic deformation and phase transformation, it is possible to establish a quantitative relation between deformation and temperature. When cells are cultured on the UNSM-treated surface, such surface can dynamically deform in response to external temperature change, and therefore apply controllable mechanical force to cells. Through this study, we demonstrate a novel way to fabricate a low-cost surface actuator that has the potential to be used for high-throughput cellular mechanotransduction.